Fuzzy Logic Based Environment Control of Operation Theatre - et. al., Sakshi Srivastav, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is very critical and important to maintain the appropriate climatic conditions in the operation theatre. In paper, we present an approach to control total environmental conditions for the operation theatre. Generally for environmental control of operation theatre air conditioning system is installed. In operation theatre environmental parameters like humidity, temperature, oxygen and particles etc. have to be controlled precisely. All the environmental parameters are of nonlinear nature hence, difficult to control or model with the help of conventional control systems. Keeping in mind the complexity and nonlinearity of these parameters as fuzzy logic controller (FLC) for controlling all the environment of operation theatre has been designed. For this fuzzy logic control system temperature, micro particles, humidity & oxygen have been taken as input parameters and based on these parameters speed of AC motor as well as the speed of exhaust motor are controlled. The control system is implemented with the help of different fuzzy rules and their membership functions derived from actual conditions. The performance of the system for control of operation theatre was studied and it has been observed that the result obtained with the fuzzy logic control system provides more effective and economical control. The fuzzy logic control system has been implemented using fuzzy Tech development tool.